2017
DOI: 10.3389/fmats.2016.00058
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Oxyfluoride Nano-Glass Ceramics Doped with Pr3+ and Pr3+–Yb3+ for NIR Emission

Abstract: Pr 3+-Yb 3+ co-doped oxyfluoride glasses and glass-ceramics (GCs) containing LaF3 nanocrystals have been prepared to obtain NIR emission of Yb 3+ ions upon Pr 3+ excitation in the blue region of the visible spectrum. Two different compositions have been tested: 0.1-0.5 Pr-Yb and 0.5-1 Pr-Yb, in addition to Pr 3+ singly doped samples. The crystallization mechanism of the nano-GCs was studied by differential thermal analysis revealing that it occurs from a constant number of nuclei, the crystal growth being limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Specifically, rare-earth doped nanocrystals (RE NCs) have drawn remarkable attention in the past few decades due to their singular properties such as high photostability, narrow emission lines, long fluorescence lifetimes, and easy functionalization [1,2]. As a result, a wide variety of applications has arisen in different fields, including medicine [3] and biology [4], solar energy [5], data storage [6], and optoelectronics [7]. Amid all the aforementioned fields, optics could be considered the most popular one due to the noteworthy number of applications, like fiber lasers and amplifiers [8], cathode ray tubes [9], plasma display panels [10], field emission displays [11], or fluorescence lamps [12] to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, rare-earth doped nanocrystals (RE NCs) have drawn remarkable attention in the past few decades due to their singular properties such as high photostability, narrow emission lines, long fluorescence lifetimes, and easy functionalization [1,2]. As a result, a wide variety of applications has arisen in different fields, including medicine [3] and biology [4], solar energy [5], data storage [6], and optoelectronics [7]. Amid all the aforementioned fields, optics could be considered the most popular one due to the noteworthy number of applications, like fiber lasers and amplifiers [8], cathode ray tubes [9], plasma display panels [10], field emission displays [11], or fluorescence lamps [12] to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, GCs have been further investigated because their luminescence properties may be increased by the crystalline environment around the RE ions [20,21,22,23]. Yu et al [24,25] reported an increase of about two orders of magnitude in the emission intensity of the Er 3+ /Yb 3+ co-doped phosphate GCs compared to the correspondent as prepared glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Many oxyfluoride GCs have been prepared by the melting quenching (MQ) method 10,11 using several RE ions, as Eu 3+ , 12 Nd 3+ for its use as laser material at 1.06 lm, [13][14][15] Pr 3+ -Yb 3+ as down-converter materials, [16][17][18] and Er 3+ -Yb 3+ for up-conversion. 19,20 But MQ method presents some limitations such as the high temperature of processing that causes fluorine loss by evaporation.…”
Section: Introductionmentioning
confidence: 99%